Ideologies of Olympic Proportions: The Aboriginal Language Broadcast of the Vancouver 2010 Olympic Games - Shulist, Sarah A. (Anthropologica, 2012)
This paper considers the language ideological impli cations of the decision to broadcast the Vancouver 2010 Olympic Games in eight Aboriginal Canadian languages. Using media coverage of this decision, I consider the motivations expressed by the organizers, the representations of the event by journal ists presenting it to a predominantly non-Aboriginal audience, and public reactions to these representations. I analyze this media event as a "language ideological debate" in which compet ing discourses about language revitalization, multilingualism/ multiculturalism and identity (both Canadian and Aboriginal) reveal deep disagreement among participants with respect to the meaning, role and importance of Aboriginal languages in Canada.